The Influence of Organic Growing Media Types And Coconut Water on Potato (Solanum tuberosum L.) Shoot Cuttings of Granola Variety - Veri Wilson Toni; Eliyanti Eliyanti; Rainiyati Rainiyati (Universitas Batanghari, 2026)
Potato (Solanum tube rosum L.) is an important horticultural commodity with incre asing de mand; howe ve r, national productivity re mains low. One approach to e nhance production is through apical cutting propagation, whose succe ss is strongly influe nce d by the growing me dia and growth stimulants. This study aime d to e valuate the e ffe cts of diffe re nt type s of organic growing me dia and coconut wate r conce ntrations on the growth of Granola potato apical cuttings. The e xpe rime nt was conducte d in the Scre e n House of the Potato Se e d Ce nte r (BBI) in Kayu Aro, e mploying a two-factorial Comple te ly Randomize d De sign (CRD). The factors te ste d we re type s of growing me dia (bamboo humus, manure , and rice husk charcoal) and coconut wate r conce ntrations (0, 25, 50, 75 mL•L⁻¹). The re sults showe d that the inte raction be twe e n me dia type and coconut wate r conce ntration had no significant e ffe ct on most obse rve d parame te rs, including plant he ight, numbe r of le ave s, and numbe r of tube rs. Howe ve r, it significantly affe cte d tube r fre sh we ight. The apical cuttings use d we re four-we e k-old Granola varie ty plants de rive d from gre e nhouse cultivation. A mixture of bamboo humus, manure , and rice husk charcoal produce d the be st growth pe rformance . A coconut wate r conce ntration of 75 mL•L⁻¹ incre ase d le af numbe r, tube r count, and tube r fre sh we ight. In conclusion, the combination of organic growing me dia and coconut wate r can e nhance potato tube r yie ld, although its e ffe cts vary de pe nding on the obse rve d parame te r.